Research in economic history - Hanes, Christopher; Wolcott, Susan (Emerald, 2015)
Volume 31 of Research in Economic History (REHI) is forthcoming in April 2015. REHI is a peer-reviewed series published once a year. We cover all areas of economic history, including demography and development. Research in Economic History is a well-established and well-cited journal which has presented work by leading researchers in the field of economic history, including economists, historians and demographers.
Keywords: Economic history -- Statistics.; Economic history.; Economic indicators.; elektronické knihy; electronic books